المفاضلة بين الرواة عند عبد الله بن المبارك (دراسة نظرية تطبيقية) - Ariangga Ramadhansyah; Marwan Mas’ud; Hendri Waluyo Lensa (Universiti Sains Islam Malaysia, 2026)
Journal of Hadith Studies, Volume 10 Issue 2 Page ( 51–70)